2010
DOI: 10.1111/j.1469-7610.2009.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on the growth of early reading skills

Abstract: Background-Studies have suggested genetic and environmental influences on overall level of early reading whereas the larger reading literature has shown environmental influences on the rate of growth of early reading skills. This study is the first to examine the genetic and environmental influences on both initial level of performance and rate of subsequent growth in early reading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 32 publications
(42 reference statements)
6
54
3
Order By: Relevance
“…Our findings complement the recent behavioral genetic studies showing that rapid naming and, to a lesser extent, phonological awareness difficulties are heritable (e.g., Petrill et al, 2010;Samuelsson et al, 2007) and that the genetic effects of RAN Examining the Double-Deficit Hypothesis 24…”
Section: Examining the Double-deficit Hypothesis 23 Discussionsupporting
confidence: 73%
“…Our findings complement the recent behavioral genetic studies showing that rapid naming and, to a lesser extent, phonological awareness difficulties are heritable (e.g., Petrill et al, 2010;Samuelsson et al, 2007) and that the genetic effects of RAN Examining the Double-Deficit Hypothesis 24…”
Section: Examining the Double-deficit Hypothesis 23 Discussionsupporting
confidence: 73%
“…In the study of Walters et al (2010), most patients (about 220 out of 288 patients in the Irish sample) had an IQ of o100 and the directions of the associations were consistent with our results in patients with lower IQ. By contrast, although no IQ data were available in Hashimoto et al (2010), their patients had a high level of education with a mean of 414 years and a SD of about 2 years, who as a group were likely to have above average IQ because of the high correlation between IQ and education levels (Petrill et al (2010)). Hashimoto et al (2010) found a link between A allele and poorer cognitive function, which is similar to our results in patients with relatively high IQ.…”
Section: Discussionmentioning
confidence: 99%
“…In longitudinal studies, naming speed has proven to be rather stable and naming speed deficits appear to be persistent in nature (e.g., Powell, Stainthorp, & Stuart, 2014). Some part of this stability can be explained by genetic sources, as a strong genetic influence has been shown in RAN performance (e.g., Byrne et al, 2006;Christopher et al, 2015;Davis et al, 2001;Petrill, Deater-Deckard, Thompson, DeThorne, & Schatschneider, 2006;Petrill et al, 2010;Samuelsson et al, 2007). There is also recent research evidence for specific genes that have been associated with RAN performance (Naples, Chang, Katz, & Grigorenko, 2009), some of them the same as those previously associated with dyslexia (Rubenstein, Raskind, Berninger, Matsushita, & Wijsman, 2014).…”
Section: What Is Rapid Automatized Naming (Ran)?mentioning
confidence: 99%